Identifying and keeping your peace when dealing with narcissistic friends in university / Yusandra Md Yusoff and Emmy Nurashikin Ismail Hashim - Md Yusoff, Yusandra; Ismail Hashim, Emmy Nurashikin (Universiti Teknologi MARA, Negeri Sembilan, 2024)
“Choose those who lift you up, not those who bring you down.” When you first enrol in university, you encounter countless new people, places, and opportunities to form friendships. While some friendships will endure a lifetime, others may fade after just a semester or two. Additionally, you could occasionally run into individuals who initially seem entertaining and attractive but gradually show a selfish side that drains you. Yes, narcissistic friends are the subject of what we are discussing. A Narcissistic Friend: What Is It? Initially, narcissistic friends can be challenging to identify. You may be captivated by their charisma, confidence, and intriguing stories. But as time goes on, you will notice trends: they are attention-seekers, rarely care about your feelings, and frequently divert every conversation back to themselves, ignoring your achievements and departing from your worries.